Applicazioni Digitali per il Rilievo Laser Scanner Terrestre del sito Archeologico del II secolo a.C. nella città di TERAMO - Mastronuzzi, Giuseppe Antonio; Piscitelli, Arcangelo; Pignatelli, Cosimo; Millella, Maurilio; Tursi, Alessandra (Archeomatica, 2012)
The environmental survey with the digital technology acquisition of Terrestrial Laser Scanner (= TLS) nowadays represents a rapid and precise application in many fields of science and technology. The Terrestrial Laser Scanner technology integrated with differential GPS can be used in the geomorphological, geophysics, engineering and archeological applications. This kind of technology, joined with the classical methods of the archaeological area survey, allows us to study the site of interest with reduced approximation. The TLS survey methods, in fact, let us not only a fast acquisition of data but also the possibility to take advantage of the points cloud for a lot of the final purposes, such as the three-dimensional reconstruction of the scenario and the creation of a rendering of a particular detail.